Gut Microbiome as a Target of Intervention in Inflammatory Bowel Disease Pathogenesis and Therapy - Helal F. Hetta; Yasmin N. Ramadan; Ahmad A. Alharbi; Shomokh Alsharef; Tala T. Alkindy; Alanoud Alkhamali; Abdullah S. Albalawi; Hussein El Amin (Immuno)
Inflammatory bowel disease (IBD) is a chronic complicated inflammatory gut pathological disorder and is categorized into ulcerative colitis (UC) and Crohn’s disease (CD). Although the cause of IBD is unclear, dysbiosis of the gut microbiota is thought to be a key factor in the disease’s progression. The gut microbiome serves as a metabolic organ and promotes wellness by carrying out several biological activities. Any modification in the makeup of the gut microbiome leads to several pathological conditions, including IBD. In this review, we emphasize the key metabolic processes that control host–microbiome interaction and its impact on host health. We also discuss the association between microbiome dysbiosis (bacteriome, virome, and mycobiome) and the progression of IBD. Finally, we will highlight microbiome-based therapy as a novel and promising strategy to treat and manage IBD.